Чат-бот як засіб комунікації із користувачем - Сальнікова, Т. С. (ХНУРЕ, 2021)
Chatbots use machine learning to identify communication patterns. Through constant interaction with people, they learn to imitate real conversations and respond to verbal or written requests, helping to find answers. Due to chatbots use artificial intelligence (AI), they understand language, not just commands. Automatic communication with users is carried out using text or voice. You can just chat or discuss an important problem. In recent years, the technology of self-learning bots has been actively developing. Virtual interlocutors work with human language. Natural language processing is an acute problem of artificial intelligence.
Keywords: чат-бот